Industrial training report at Universiti Sains Malaysia Kubang Kerian 16150 Kota Bharu Kelantan / Fadila Amira Razali - Razali, Fadila Amira (Faculty of Computer and Mathematical Sciences, 2012)
The aim of this study was to determine the validity and reliability the knowledge, attitude and practice on honey questionnaire among PPSP staff at Universtiti Sains Malaysia, Kubang Kerian, Kelantan. The random sample of 148 PPSP staff aged above 18 years old were collected. The items of the questionnaire were framed from literature review and discussion from the experts. The cronbach’s alpha reliability and factor analysis were applied to measure internal consistency and construct validity respectively. The analysis was done using Statistical Package for Social Science (SPPS) version 18. A total of 148 applicants participated in this study. The factor analysis for the knowledge domain showed the items were loaded into four components with factor loading from 0.464 to 0.830. The final attitude domain has 9 items with factor loading from 0.473 to 0.863. For practice domain, there were final 5 items in the first sub domain ranged from 0.403 to 0.849. For second sub domain of practice, there were 6 final items loaded from 0.364 to 0.879. The overall Cronbach’s alpha for knowledge, attitude and practice were 0.784, 0.883 and 0.780 respectively. These findings show the validity and reliability evidence of the KAP of Honey questionnaire. Statistically, the questionnaire is generally valid and reliable to measure the knowledge, attitude and practice on honey consumption. However, further expert review on each item importance followed by remove and retest is suggested to improve the questionnaire